Safety and efficacy results of simulated post-exposure prophylaxis with human immune globulin (HRIG; KEDRAB) co-administered with active vaccine in healthy subjects: a comparative phase 2/3 trial - Mark A. Matson; Eran Schenker; Michal Stein; Vladislava Zamfirova; Huy-Binh Nguyen; Garrett E. Bergman (Taylor & Francis Group, 2020)
We conducted a clinical trial to assess the safety and putative efficacy of an additional human rabies immune globulin (HRIG; KEDRAB) versus an older product (Comparator, HyperRAB S/D® [Grifols]) and determine whether HRIG interferes with development of endogenous antibodies versus Comparator, when each is given with an active rabies vaccine. This was a prospective, double-blind, single-period, non-inferiority study in which subjects were randomized (1:1) to a single dose (20 IU/kg) of HRIG or Comparator on day 0 and rabies vaccine (RabAvert® [GlaxoSmithKline]; 1 mL of ≥2.5 IU/mL) on days 0, 3, 7, 14, and 28. Anti-rabies antibodies were measured by rapid fluorescent focus inhibition test on day 14, and subjects were followed until day 185. Rabies virus neutralizing antibody (RVNA) titers ≥0.5 IU/mL were considered seroconversion putatively indicative of protection. The non-inferiority criterion was the lower limit of the 90% confidence interval (CI) >-10%, for the between-group difference in the proportion of subjects achieving RVNA ≥0.5 IU/mL. On day 14, 98.3% of 59 subjects in the HRIG group and 100% of 59 in the Comparator group had RVNA ≥0.5 IU/mL (difference between proportions - 1.8%; 90% CI, - 8.2, 3.1; non-inferiority criterion met). One subject in the HRIG group did not meet the seroconversion criteria for anti-rabies antibody, and one subject in the Comparator group showed an anamnestic response, with much higher than expected anti-rabies antibody levels at both baseline and on day 14. Thus, HRIG allows for prophylactic anti-rabies antibody titers and is non-inferior to Comparator, when administered with rabies vaccine.